Deliberative characteristics of Brazilian conversations about the [not] decriminalization of abortion in Argentina - RIZZOTTO, Carla Candida (2021)
This article proposed to discuss the repercussion the debate about the decriminalization of abortion in Argentina in Brazilian social networks from the analysis of 3207 comments in Facebook posts of the newspapers’ fanpages El País, Estadão and O Globo. Based on the theory of deliberation, through a content analysis, this article identified in the comments in question the manifestation of the variables positioning, type of thought, speech shift, theme, form, rationality, source, rhetorical strategy and resources arguments. The results point to a strong polarization and high levels of conflict. There is predominance of rational comments, and the main source of justification are personal experiences and values.